Zero Measure Sraffian Economies: New Insights from Actual Input–Output Tables†. (13th May 2022) - Mariolis, Theodore; Veltsistas, Panagiotis
Abstract: New theoretical and empirical evidence reveals that the actual input–output table economies of single production, which are usually studied in the value–capital theory literature, are almost similar to non-diagonalizable, triangular and both uncontrollable and unobservable (in the sense of Kalman) economies producing only one basic commodity and non-self-reproducing non-basics (in the sense of Sraffa), the immense majority of which are pure consumption commodities. Since (i) these basic commodities are the corresponding Sraffian Standard commodities of the original economies; (ii) the resulting empirical probabilities of non-monotonic price–profit rate curves and re-switching of techniques are by no means negligible; and (iii) systems and matrices are almost always completely controllable/observable and diagonalizable, respectively, it follows that the said actual input–output table economies are not only Sraffian but also of almost zero measure.